Pengaruh Penerapan Media Berbasis Discovery Learning ECO AR 1-3 terhadap Pemahaman Konsep Ekologi Siswa SMA - Ila Maryama1; Puguh Karyanto1; Yudi Rinanto1; Lanang Kuntadi2 (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The research was conducted to know the influence of media-based discovery learning ECO AR 1-3 towards understanding the ecology material concept at high school students. Research carried out by using the ex post facto method and posttest only control group design. The sampling used was cluster random sampling. They were the students of SMAN 2 Karanganyar who had received the ecosystem material. Data collection was done through observation, documentation, and tests. The data analysis techniques in qualitative and quantitative include instrument NEP attitude and knowledge, normality test, homogeneity test, and independent sample t-test test. Data analysis was assisted with IBM SPSS 21 program. The results showed that (1) ECO-AR 1-3 improves the understanding of the environmental literacy concept in high school students, (2) Both the attitude and knowledge questioner  through homogeneity and normality test show good results and decent as teaching material in order to increase environmental literacy in high school students, (3) the results of the independent sample t-test and both attitude and knowledge questioner show the significance value less than 0.05 so that H0 is rejected and the H1 is accepted.